2017
DOI: 10.1002/pc.24477
|View full text |Cite
|
Sign up to set email alerts
|

Open‐hole tensile behaviour and failure prediction of carbon fibre reinforced aluminium laminates

Abstract: In this article, the open‐hole tensile behaviour of carbon fibre reinforced aluminium laminates (CARALL) were investigated experimentally and numerically. Two specimens with different fibre orientations ([0°/90°/0°] and [45°/0°/−45°]), consisting of T700 carbon fibre/epoxy prepreg and 2024‐T3 aluminium with a 3/2 configuration, were manufactured by the autoclave process. Damage initiation and progression were considered in modelling the CFRP layers and interface bonding layers. Isotropic hardening behaviour wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Based on the continuum damage mechanics model, a composite material constitutive model is established for the analysis of the damage evolution of ribs and skins. The damage variable of the material is expressed in the form of a tensor, and the constitutive relationship of the composite material can be expressed as the following form: where is stress, strain and matrix of stiffness under the principal axis of material damage 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the continuum damage mechanics model, a composite material constitutive model is established for the analysis of the damage evolution of ribs and skins. The damage variable of the material is expressed in the form of a tensor, and the constitutive relationship of the composite material can be expressed as the following form: where is stress, strain and matrix of stiffness under the principal axis of material damage 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the GL-45 /À45 specimens exhibit stress reduction mechanisms upon surpassing their ultimate stress, with damage primarily arising from a combination of tensile and shear stresses. 10,12,32 It is important to acknowledge that the stress-strain curves demonstrate bi-linearity, with consistent slopes during the initial linear phase irrespective of the layup. Nevertheless, the slopes diminish to a greater extent in the second linear phase for larger hole sizes (D = 7, 9 mm) compared to smaller ones (D = 3, 5 mm).…”
Section: Mechanical Behaviors Of Open-hole Glarementioning
confidence: 99%
“…This type of damage is recognized as a tensile-dominated damage mode. 10,12 Figure 4C illustrates that when the strain reaches 97% of the failure strain, noticeable cracks perpendicular to the loading direction become visible at the hole edges of the GL-45 /À45 specimens, and subsequently propagate toward the specimen edges. At the point of ultimate failure, it was observed that the crack extension path of the aluminum alloy in the GL-3-45 /À45 specimen aligned with the direction of fiber layup, whereas the crack extension path in the GL-9-45 /À45 specimen remained perpendicular to the load direction.…”
Section: Failure Characteristics Of Open-hole Glarementioning
confidence: 99%
“…Numerical methods could also act as an useful tool for understanding the complex interacting failure mechanisms in composite materials. [12][13][14] Andrea Sellitto et al [15] established a progressive damage model and determined the proper modeling parameters for predicting the intra-laminar and inter-laminar damage onset and propagation of carbon-fiber laminate under LVI. Riccio et al [16] adopt an advanced numerical model to predict the dynamic responses and damage features of fuselage under field drop test.…”
Section: Introductionmentioning
confidence: 99%